Integer Interval Value of Milne’s Predictor and Milne’s Corrector Method for First Order ODE - Arul Dass, A.; Veeramalai, G. (International Journal of Engineering and Technology, 2018)
In this paper A new approaches to solve the approximate Â Â solution of Â Â the initial value problem for the first order ordinarydifferential equations and the solution can be used to computeÂ y numerically specified the value of Â Â Â near to in theÂ interval analysis method and also used Milneâ€™s predictor and correctorÂ for interval. In interval method gives a more accurate theapproximate solution of life situation and numerical illustration are givenÂ